Exact Transport Representations of the Classical and Nonclassical Simplified PN Equations. Issue 4 (19th September 2018) - Makine, I.; Vasques, R.; Slaybaugh, R. N.
Abstract: We show that the recently introduced nonclassical simplified PN equations can be represented exactly by a nonclassical transport equation. Moreover, we validate the theory by showing that a Monte Carlo transport code sampling from the appropriate nonexponential free-path distribution function reproduces the solutions of the classical and nonclassical simplified P N equations. Numerical results are presented for four sets of problems in slab geometry.